FAKTOR YANG MEMPENGARUHI KEJADIAN DERMATITIS DI DESA PEMATANG JOHAR KECAMATAN LABUHAN DELI KABUPATEN DELI SERDANG - Silalahi, Novrika; Malau, Pitto Pratiwi (Jurnal Penelitian Kesmasy, 2025)
This study discusses the factors associated with the occurrence of dermatitis. Dermatitis is inflammation of epidermis and dermis which is characterized by objective symptoms of polymorphic lesions and symptoms subjective itching, it is caused by endogenous or exogenous factors. Globaly dermatitis affect 230 million peoples in 2016 or 3,5% of the world population, the incidence of dermatitis in pematang johar villages in November 2018 reached 453 cases while in Hamlet Gunung Sinar there were 153 cases. The type of quantitative research with the method that used was analytical survey with cross sectional approach. The research was conducted from April to June 2024 with a sample of global cases of dermatitis as many as 60 people, the study was carried out through interviews with questionnaires. The results of the study were 60 respondents with dermatitis as many as 31 peoples (51.7%). As many as two of the three factors studied with chi-square test was 95% confidence level it had a significant relationship with dermatitis, namely chemical contact with p-value 0.035, and environment conditions with p-value 0.001, while one factor namely personal hygiene did not indicate a meaningful relationship. So the researcher expects that the public must pay more attention and maintain environmental conditions, so that it is expected to prevent the occurrence of dermatitis.